Effect of haruan (channa striata) extract on fibroblast cells count in wound healing - Ardi Siswanto; Nurdiana Dewi; Lisda Hayatie (Journal of Dentomaxillofacial Science, 2016)
Haruan is Kalimantan’s indigenous fish which has the potency to accelerate wound healing. Haruan extract has substantial properties such as albumin, Zn, Cu, and Fe to accelerate wound healing. The purpose of this study is to assess the effect of haruan extract on wistar rat’s buccal mucosa wound healing on day 3, 5, and 7 histopathologically. This study was experimental with post-test with control group design. Samples were consisted of 4 treatment groups, 25%, 50%, 100% haruan extract treatment groups and negative control treated with aquadest for 7 days. Mean fibroblast cells count reached its peak on day 7. Mean fibroblast cells count in each group was 26.995; 40.500; 49.165; 24.495 respectively. Two way ANOVA and Post Hoc Least Significant Difference tests indicated there was a significant difference (p<0.05) between haruan extract treatment group and negative control. In conclusion, haruan extract treatment significantly increase fibroblast cells count in wound healing process.